Small RNA mediated regulation of seed germination - Das, Shabari Sarkar; Karmakar, Prakash; Nandi, Asis Kumar; Sanan-Mishra, Neeti (Frontiers in Plant Science, 2015)
Mature seeds of most of the higher plants harbour dormant embryos and go through the complex process of germination under favourable environmental conditions. The germination process involves dynamic physiological, cellular and metabolic events that are controlled by the interplay of several gene products and different phytohormones. The small non-coding RNAs comprise key regulatory modules in the process of seed dormancy and germination. Recent studies have implicated the small RNAs in plant growth in correlation with various plant physiological processes including hormone signalling and stress response. In this review we provide a brief overview of the regulation of seed germination or dormancy while emphasising on the current understanding of the role of small RNAs in this regard. We have also highlighted specific examples of stress responsive small RNAs in seed germination and discussed their future potential.